(3JWHjb GdbGfhf GdLfGFj ef MjK GdReGf (B: s (3aj VhA GdTQYjI GdLfGFjI (B/ s - (3Lejd aDGO eMeO MSfs; (3MSfjf EHQGgje UGdM YjO (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JfGhdJ GdQSGdI GdJYQjaGJ GdeNJdaI ddbGfhf GdLfGFi h CSHGH GdQSGdI GdJi Jcef ai GdJVGQH ef CMcGe eMceI GdfbV GdLfGFi h GdOSJhQjI GdYdjG YbH UOhQ GdbGfhf (B17 (3dSfI (B1999 (3h GdbGfhf (B4 (3dSfI (B1996(3e h JgOa GdQSGdI dEjLGO bhGYO edReI dSdWGJ GdOhdI GdKdGKI Jcef ai eHOC GdTQYjI GdLfGFjI h dgPG HOCJ GdQSGdI HOQGSI GdaQb Hjf JfGRY GdbhGfjf GdLfGFjI h GdUhQ GdCNQi GdeNJdaI YfgG Ke GfJbdJ GdQSGdI Edi OQGSI GdbGYOI GdbGfhfjI GdLfGFjI GdCShC ddeJge h GdbGYOI GdbGfhfjI GdLfGFjI GdCUdM ddeJge h GdbGYOI GdbGfhfjI GdLfGFjI GdfGSNI h GdbGYOI GdbGfhfjI GdeDbJI h GdGSJFfGKjIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2010.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdTQYjI GdLfGFjIs; (3bhGfjf GdJehjf hGdJSYjQIs; (3GdTQYjI GdELQGFjIs; (3GdGOYGA GdeHGTQs; (3GfbVGA GdOYhi GdLfGFjIs; (3GdJMQj hLeY GdGSJOdGdGJs; (3GdbGfhf (B174 (3dSfI (B1998s; (3eMGce Cef GdOhdIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs